Factors influencing choice of a university by students in Zimbabwe - Mupemhi, Shepard (Academic Journal, 2017)
This paper discussed factors that influence choice of a university by students in Zimbabwe. A cross-sectional qualitative design involving the use of focus groups is used. The research revealed that choice of a university brand is influenced by a number of internal factors such as the quality of programmes offered by the institution, the brand name of institution, state of facilities, location of university, level of tuition fees, relationships and networks with stakeholders, and university visibility through communications. The implications are that universities should be treated as brands. The management focus should be on those attributes that form the core, tangible, augmented and potential components of the university brand.